Inflammatory bowel disease‐related periostosis. Issue 2 (6th June 2022) - Yuan, Yilin; Mu, Rong
Key point: Periosteal reaction and bone absorption could be manifested in ulcerative colitis. Abstract : A 61‐year‐old patient with inflammatory bowel disease presented with multiple sites of severe perosteal reacton and bone aborption on plain radiology.